2014
DOI: 10.1371/journal.pntd.0003138
|View full text |Cite
|
Sign up to set email alerts
|

The Spatial Dynamics of Dengue Virus in Kamphaeng Phet, Thailand

Abstract: BackgroundDengue is endemic to the rural province of Kamphaeng Phet, Northern Thailand. A decade of prospective cohort studies has provided important insights into the dengue viruses and their generated disease. However, as elsewhere, spatial dynamics of the pathogen remain poorly understood. In particular, the spatial scale of transmission and the scale of clustering are poorly characterized. This information is critical for effective deployment of spatially targeted interventions and for understanding the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 22 publications
1
43
0
Order By: Relevance
“…Previous work using case data has focused on the spread of dengue within urban or rural communities [79] or the dispersion of the virus across a country [6]. These studies have demonstrated micro-scale spatial dependence between cases at distances of under one kilometer in both rural Northern Thailand and Bangkok suggesting focal transmission in these settings but also waves of dengue incidence coming out of Bangkok [7, 8, 10].…”
Section: Introductionmentioning
confidence: 99%
“…Previous work using case data has focused on the spread of dengue within urban or rural communities [79] or the dispersion of the virus across a country [6]. These studies have demonstrated micro-scale spatial dependence between cases at distances of under one kilometer in both rural Northern Thailand and Bangkok suggesting focal transmission in these settings but also waves of dengue incidence coming out of Bangkok [7, 8, 10].…”
Section: Introductionmentioning
confidence: 99%
“…The ϕ clustering statistic [ϕ(d 1 , d 2 )] is defined as the probability of two deaths occurring in a defined spatial and temporal window relative to the independent probabilities of observing two deaths within the spatial window or within the temporal window (29,30) ϕðd 1 , d 2 Þ = Prðj ∈ Ω i ðd 1 , d 2 , t 1 = 0, t 2 = 1ÞÞ Prðj ∈ Ω i ðd 1 , d 2 , · ÞÞPrðj ∈ Ω i ð · , t 1 = 0, t 2 = 1ÞÞ , where Ω i (d 1 , d 2 , t 1 = 0, t 2 = 1) is the set of all influenza deaths occurring both within the (d 1 , d 2 ) spatial window of case i and within 1 wk (t 1 = 0, t 2 = 1) of case i. Window size (d 2 − d 1 ) was kept constant at 100 m, and d 2 ranged from 100 m to 2.5 km; 95% CIs were calculated using the 2.5 and 97.5 percentiles of 1,000 bootstrap samples.…”
Section: Methodsmentioning
confidence: 99%
“…1). We used the spatiotemporal clustering statistic, ϕ(d 1 , d 2 ), to characterize spatial and temporal dependence of individual deaths (28,29). This statistic estimates the probability of any two deaths occurring within the same week and within a spatial window of one another relative to the expectation if spatial clustering and temporal clustering were independent (Methods).…”
Section: Reproduction Number Estimates and Association With Sociodemomentioning
confidence: 99%
“…We rarely observe infection pairs (i.e., who infected whom) in a transmission network. Where only a minority of cases are observed, analyses tend to be restricted to characterizing the spatial and temporal scales at which cases tend to occur together but the relationship between spatial clustering and transmission distance is complex (Bhoomiboonchoo et al, 2014; Grabowski et al, 2014; Lin et al, 2011; Morrison et al, 1998; Salje et al, 2015; 2012). Only where we have been able to observe the majority of cases in a transmission network or we have detailed epidemiological data on who infected whom, has estimation of mean transmission distances previously been possible (Assiri et al, 2013; Ferguson et al, 2001a; Keeling et al, 2004).…”
Section: Introductionmentioning
confidence: 99%